2016
DOI: 10.5897/ajmr2016.8266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunoglobulin Y (IgY) serum against plaque bacteria

Abstract: Dental caries is an infectious disease caused by plaque bacteria, especially Streptoccus mutans. Many studies were conducted to develop methods or material for dental caries prevention. It was using passive immunization that will produce specific antibodies. Yolk immunoglobulin (IgY) is antibody in the serum and egg yolk. This study aimed to determine the effect of IgY serum against the growth of dental plaque bacterial in vitro. In the long term, it is expected IgY specific S. mutans can be as one of material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Specific IgY has also been used against pathogenic bacteria of the oral cavity, including Streptococcus mutans and Porphyromonas gingivalis ; published works have shown that these antibodies can inhibit the development of caries, accumulation of dental plaque, and reinfections [ 17 , 43 , 44 ]. Furthermore, IgY has also helped in the treatment of other oral pathologies, such as periodontitis and halitosis [ 45 ].…”
Section: Igy In the Diagnosis And Treatment Of Diseasesmentioning
confidence: 99%
“…Specific IgY has also been used against pathogenic bacteria of the oral cavity, including Streptococcus mutans and Porphyromonas gingivalis ; published works have shown that these antibodies can inhibit the development of caries, accumulation of dental plaque, and reinfections [ 17 , 43 , 44 ]. Furthermore, IgY has also helped in the treatment of other oral pathologies, such as periodontitis and halitosis [ 45 ].…”
Section: Igy In the Diagnosis And Treatment Of Diseasesmentioning
confidence: 99%